Assessment of Some Heavy Metal Concentrations in Drilling Mud samples in Az Zubair Oil Field, Basra, Iraq - Sahar Amin; Abdul Hamid Al- Obiady; Rana Alani; Athmar Al-Mashhady (Engineering and Technology Journal, 2018)
Analysis of eight heavy metal concentrations (Cd, Cr, Cu, Fe, Mn,Ni, Pb and Zn) of 14 drilling mud samples collected from oil well at differentdepths which is located in AZ Zubair oil field-Basra was done in this study .The samples were measured using atomic absorption spectrophotometry.Obtained results indicated that the heavy metal concentrations range from thelowest value of 1.66mg/kg for Cd to the highest value of 1235.86mg/kg forFe. The abundance trend for the heavy metals concentration was in thedescending order of Fe, Mn, Ni, Cu, Cr, Zn, Pb, and Cd. Four parameters:Enrichment Factor (EF), Contamination Factor (CF), Geo-accumulationIndex (Igeo) and Pollution Load Index (PLI) were assessed in order toevaluate the degree of contamination.